Exploring the development of Australian general practice nursing: Where we have come from and where to from here? - Halcomb, E.; Davidson, Patricia; Patterson, E. (eContent Management, 2007)
Significant development has occurred in the role and scope of Australian general practice nursing in the last decade. Although there has been a nursing presence in Australian general practice for many years (Linn 1977), current workforce shortages and the growing need for chronic and complex disease management and provision of preventive health care in the community have fuelled role development (Halcomb, Patterson & Davidson 2006). In an effort to explore and document the evolution of scholarship and professional development in Australian general practice nursing a content analysis of the proceedings of the four Australian practice nursing conferences was undertaken.This framework allows the mapping of the trajectory related to professional development issues, policy, research and scholarship. Content analysis revealed that the papers presented at each of the four conferences could be broadly divided into six major themes, namely: (1) role of the practice nurse, (2) education and training, (3) research, (4) legal, ethical and risk issues, (5) innovation in clinical practice, and (6) operational and management issues in general practice. Documenting the evolution of this emerging specialty is important in planning initiatives to maximise practice nurses’ important contribution to primary health care.